2006
DOI: 10.1002/app.24752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyhedral oligomeric silsesquioxane coatings on the interface and impact properties of carbon‐fiber/polyarylacetylene composites

Abstract: Two kinds of polyhedral oligomeric silsesquioxane (POSS) coatings were used for the modification of the interface in carbon fiber (CF) reinforced polyarylacetylene (PAA) matrix composites. The effects of the organic-inorganic hybrid POSS coatings on the properties of the composites were studied with short-beam-bending, microdebonding, and impact tests. The interlaminar shear strength and interfacial shear strength showed that the POSS coatings resulted in an interfacial property improvement for the CF/PAA comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In a previous study, our group has improved the interfacial properties of non-polar and brittle polyarylacetylene composites through covering the fiber surface with POSS by solution dipping method. 41 However, POSS particles did not form any chemical bonding with the fibers and polyarylacetylene matrix. In addition, whether POSS has an effect on the interfacial properties of tough matrices is not clear.…”
Section: Introductionmentioning
confidence: 96%
“…In a previous study, our group has improved the interfacial properties of non-polar and brittle polyarylacetylene composites through covering the fiber surface with POSS by solution dipping method. 41 However, POSS particles did not form any chemical bonding with the fibers and polyarylacetylene matrix. In addition, whether POSS has an effect on the interfacial properties of tough matrices is not clear.…”
Section: Introductionmentioning
confidence: 96%
“…POSS chemically bonded with thermoset polymers either enhances or reinforces the mechanical and thermal properties of the neat material system [15]. Recent studies by Zhang [16] have demonstrated 25–27% improvement of the interlaminar shear strength with various POSS products. It is therefore expected that if POSS particles, with appropriate functional groups, can be installed on the carbon fiber surface, they would provide a stable and strong F/M interface [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This addition polymerization improves the thermal stability and oxidation characteristics of PAA. The char yield of the PAA resins can reach approximately 85–90 wt % when they are heated to high temperatures in an inert atmosphere 4, 5…”
Section: Introductionmentioning
confidence: 99%